Entrepreneurial Healthcare Education in the Muhammadiyah Wiyung Community - Halimatus Sa’diyah; Siti Afiqah Binti Zainuddin; Evi Dwi Kartikasari; Elfida Naila Fauziah Nazlie; Irwansyah (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
The "Entrepreneurial Health Care Education in the Muhammadiyah Wiyung Community" initiative aims to enhance health awareness and entrepreneurial spirit among community members, particularly the elderly. Conducted from July to August 2024, this community service program utilized a mentoring approach that included counseling, health assessments, and business plan development. Participants received free health checks, including blood pressure and blood sugar tests, along with consultations on maintaining a healthy lifestyle. The program also focused on fostering entrepreneurship by assisting community members in creating business plans for a stall selling essential goods. Despite challenges such as limited product variety and offline marketing, the initiative successfully engaged around 50 participants, promoting a healthier lifestyle and entrepreneurial mindset. The collaboration between the service team and community leaders was instrumental in achieving the program's objectives. The findings suggest that ongoing community service efforts can significantly contribute to the development of healthy, productive, and entrepreneurial individuals within the Muhammadiyah Wiyung community. Future recommendations include expanding product offerings and incorporating e-commerce strategies to enhance business viability.